Costs of caring for children with an intellectual developmental disorder. Issue 4 (October 2015) - Genereaux, Dallas; van Karnebeek, Clara D.M.; Birch, Patricia H.
Abstract: Background: Caring for a child with intellectual developmental disorder (IDD) is expensive for the medical system, for the family, and for society in general. Whereas the health care costs of IDD have been described, the societal and parental costs of IDD have been less well documented. Objective: Our goal was to estimate the out-of-pocket costs to parents, and the non-health system costs to society, of raising a child with IDD. Methods: We used an online retrospective survey, previously developed by our group, to collect parental and societal costs to families of 80 children who presented with IDD of unknown etiology in British Columbia, Canada. Results: Median annual parental costs of caring for 80 children with IDD was CAD44, 570 (range CAD2245–225, 777). The largest contributors to parental costs were income loss and caregiving time costs. Median annual societal costs (excluding health system costs) were CAD27, 428 (range CAD0–119, 188). In school age children, the largest contributor to societal costs was a per child school subsidy. Both parental and societal costs increased with increasing IDD severity. Parental costs were not adequately compensated by government benefits received. Conclusions: Although medical care is universally available through Canadian provincial health systems and social assistance is provided to the families of children with IDD, parents continue to bear a substantial financial burden beyond that associated with raising an unaffected child.